ẢNH HƯỞNG CỦA MẬT ĐỘ NUÔI ĐẾN TỐC ĐỘ LỌC CỦA HÀU THÁI BÌNH DƯƠNG Crassostrea gigas (THUNBERG, 1793) - Nguyễn, Minh Hiếu; Hoàng, Trung Du; Nguyễn, Hữu Huân; Phan, Minh Thụ; Nguyễn, Trịnh Đức Hiệu; Võ, Hải Thi; Phạm, Thị Miền; Nguyễn, Kim Hạnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INFLUENCE OF STOCKING DENSITY ON FILTRATION RATE BY Crassostrea gigas (THUNBERG, 1793) Pacific Oysters (Crassostrea gigas) is an introduced species form Japan and is raised in Vietnam waters. Relatively little is known about effect of stocking density on oyster filtration rate. So, the goal of this study investigates the filtration rate of Pacific oyster based on variation of the oyster density. The study was carried out with adult oysters of similar shell size (range from: 7.0-9.8 cm; average: 8.28±0.51 cm) collected in Nha Phu lagoon, Khanh Hoa province. The first order kinetic model and the composite exponential kinetic model were used to estimate oyster filtration rate (FR) based on the reduction of algal density over time. In which, the composite exponential kinetic model is more suitable than the first order kinetic model to estimate the Pacific oyster filtration rate (provide algal once-initial). The results of both models showed that oysters at low density gave a better filtration rate than oysters at high density and that this filtration rate was maximum: 1.28 (L/hr/g dry).